ANALISIS WACANA KRITIS BERITA â€œKEMATIAN TERDUGA TERORIS SIYONOâ€ DI HARIAN SOLOPOS - Fathan Dj (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2018)
CDA of Fairclough model is applied to investigate the news of the death of Siyono, the suspected terrorist in SoloPos newspaper. Three levels of analysis are used to criticize the discourse, namely texts, discourse practice, and sociocultural practice. It reveals that SoloPos chooses some words that tend to be more neutral in the news. SoloPos has also the independent position in exposing the news without any intervention from other parts. It seems helps to create condusive andÂ peaceful circumstances in Solo in informing the news to the society.